MXenes: advances in the synthesis and application in supercapacitors and batteries - Wasnik, Kundan; Pawar, Meenakshi D.; Raphael, Leya Rose; Pullanchiyodan, Abhilash; Shelke, V. Manjusha; Raghavan, Prasanth (Journal of Materials Research, 2022)
MXenes, the newest family member of the two-dimensional materials have been widely investigated for different applications, particularly in the energy storage realm. With regard to this, MXene precursors have attained widespread attention for the application in electrochemical energy storage devices especially supercapacitors and batteries. This review has comprehensively studied various synthesis strategies adopted for MXenes including the top-down and bottom-up approaches. The shift to renewable energy alternatives have focused on the electrochemical choices such as supercapacitors and batteries, the most common and relevant ones. Thus the application of MXenes and its composite in supercapacitors as electrodes have been analyzed along with its detailed mechanism and electrochemical performance. Several battery chemistries including lithium-ion, sodium-ion and other battery systems utilizing MXenes have also been discussed here. Thus the existing strategies, advancements, and drawbacks regarding the inclusivity of MXenes in the electrochemical energy systems of supercapacitors and batteries are reviewed in this article.

Molecularly engineered PW12@Polypyrrole/MXene composite for high-energy, high-rate lithium-ion capacitor - Pawar, Meenakshi D.; Pandey, Priyanshi; Shelke, Manjusha (Journal of Energy Storage, 2026)
Due to inherent differences in the charge storage mechanisms of anode and cathode in a hybrid lithium-ion capacitor (LIC), a significant kinetic balance exists, necessitating the need to improve the ion/electron transfer capability of anode materials. In this study, we have developed a ternary pseudocapacitive composite comprising redox-active phosphotungstic acid nanoclusters (PW12) anchored to polypyrrole nanofibers (PPy), which are further decorated with Ti3C2Tx MXene (PW12@PPy/Ti3C2Tx) synthesized via an in-situ polymerization strategy. Here, Ti3C2Tx MXene serves as a conductive scaffold for PW12 wrapped PPy nanofibers, promoting efficient electron/ion transport. Simultaneously, the incorporation of PW12-anchored PPy nanofibers effectively mitigates the natural tendency of MXene to restack, thus preserving its layered structure. The PW12@PPy/Ti3C2Tx hybrid composite material delivers a high specific capacity of 767 mAh g-1 at 0.1 A g-1 after 100 cycles and a promising cycling stability of 280 mAh g-1 at 1 A g-1 up to 600 cycles. Moreover, an assembled LIC device using PW12@PPy/Ti3C2Tx as anode with nitrogen-doped sucrose carbon (NSC) as cathode demonstrates the highest energy density of 125 Wh kg-1 and maximum power density of 17,058 W kg-1. The device also maintains good cycling stability of 78.4 % capacity retention after 10,000 cycles at 1 A g-1. These results highlight a promising pathway for designing MXene-based hybrid composites with enhanced lithium storage performance, effectively addressing the kinetic mismatch challenges in LIC anode applications.
Keywords: Full cell device; Li ion diffusion; Lithium-ion capacitor; MXene; polyoxometalates; polypyrrole